UPAYA PENINGKATAN HASIL BELAJAR SISWA DENGAN MENERAPKAN PEMBELAJARAN KONSTRUKTIVISTIK - Akhrianto, Akhrianto (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2017)
The aims of this study is to improve the learning outcomes of economics, especially the results of learning about employment, develop economic learning activities in accordance with the desired curriculum 2013, and is an effort to innovate in learning according to the needs of the school, especially in improving the quality of learning outcomes. In cycle one student participation when learning begins to appear when compared to PTK, students discipline work on assignments (based on the recognition of students not infrequently still studying in lll Economics study hours to do group assignments), students appear to be happy during learning. This excitement has an impact on students' enthusiasm, so that the results of the posttest increase from the pretest (the average pretest is 43.31 to 73.22). In the second cycle the students were very enthusiastic about the learning activities (students did not seem to move from their seats even though the researchers had ordered to leave the classroom, students were more active during the learning process, students became more creative, this can be seen from the way they present scientific reports, compiling maps concepts, as well as in carrying out other group activities, Students become more communicative. The concentration of students in learning is quite high. This can happen because researchers always bring students into problem orientation before core learning begins, and student learning outcomes have increased from cycle I (from on average 73.22 to 81.89 and classical learning completeness from 81.08% to 88.89%. Thus it can be concluded that by applying constructivist learning can improve student learning outcomes.